2009
DOI: 10.1007/s10439-009-9696-z
|View full text |Cite
|
Sign up to set email alerts
|

The Mandibular Cartilage Metabolism is Altered by Damaged Subchondral Bone from Traumatic Impact Loading

Abstract: Osteoarthritis (OA) in the temporomandibular joint (TMJ) is a degenerative disease caused by excessive external loading. Recently, it was reported that the damage in the mineralized subchondral bone caused by traumatic impact-loading is responsible for the initiation and progression of cartilage degeneration. Thus far, we have hypothesized that cytokines released from damaged subchondral bone from impact-loading affect the cartilage catabolism under pathological conditions. An impactor of 200 gw was dropped on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 38 publications
4
14
0
1
Order By: Relevance
“…More interestingly, when co‐cultured with stressed chondrocytes or osteoblasts, the expression of type II collagen, aggrecan , and SOX‐9 mRNAs in chondrocytes was markedly lower than when chondrocytes were co‐cultured with unstressed chondrocytes or osteoblasts, respectively. These results were very similar to those reported in previous studies (28, 30, 31). Therefore, soluble mediators secreted from the co‐cultured osteoblasts could suppress chondrocyte‐specific markers (30, 31), and in another previous report, GAG synthesis in chondrocytes was significantly reduced in a model in which chondrocytes and osteoblasts were co‐cultured together in direct physical contact (28).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…More interestingly, when co‐cultured with stressed chondrocytes or osteoblasts, the expression of type II collagen, aggrecan , and SOX‐9 mRNAs in chondrocytes was markedly lower than when chondrocytes were co‐cultured with unstressed chondrocytes or osteoblasts, respectively. These results were very similar to those reported in previous studies (28, 30, 31). Therefore, soluble mediators secreted from the co‐cultured osteoblasts could suppress chondrocyte‐specific markers (30, 31), and in another previous report, GAG synthesis in chondrocytes was significantly reduced in a model in which chondrocytes and osteoblasts were co‐cultured together in direct physical contact (28).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, it is of great interest that microcracks in the subchondral mineralized tissue caused by overloading can contribute to the initiation of vascular invasion into the articular cartilage (27), which indicates a possible way in which cytokines may be trafficked, and may subsequently lead to the degeneration of cartilage. As for the mandibular condyle, it was reported that external loading, such as a traumatic impact, induced serious damage in the boundary layer between cartilage and subchondral bone (28). From these considerations, subchondral bone may play a crucial role in OA pathogenesis following either biomechanical or biological pertubations.…”
Section: Discussionmentioning
confidence: 99%
“…Swine models are currently being used in multiple medical and surgical disciplines, [33][34][35][36] suggesting that swine models as a proxy for human conditions are reasonable. Further benefits to the use of swine, include recent completion of the swine genome project, with steady increases in the number of swine transgenic models, 37,38 including a green fluorescent protein model 39 and a severe combined immunodeficiency model 40 ; these models yield exciting possibilities for preclinical trials in swine that were previously limited to rodent and primate models.…”
Section: Discussionmentioning
confidence: 99%
“…37,[41][42][43] Anatomic similarities between swine and humans in body size, maxillary bone anatomy, TMJ function 23 ; bone remodeling, regeneration, and cortical bone mineralization, and critical-sized bone defects, 44 also suggest that swine craniofacial models that mimic human conditions are also appropriate. Several swine models exist for use in craniofacial conditions including mandibular reconstruction, 33 post traumatic conditions, 36 cranial defects, 35 and nasal and Because weight significantly varied for 5-week-old piglets, a normalized defect size was established. Normalization was weight based, and created based on the knowledge that the 2 cm defect in a pig weighing 10.8 kg did not heal.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the actual cartilage layer in an explant is 1–2 mm. More, the development of osteoarthritis has been demonstrated after impact on the subchondral bone, without affecting the cartilage surface (Donohue et al, 1983; Lahm et al, 2004, 2006; Lin et al, 2009). Incorporating the different physical properties of bone and different cartilage layers will alter the stress/strain fields that are used as impact input and, along with the biochemical effect of trauma to the subchondral bone, is the subject of future work.…”
Section: Discussionmentioning
confidence: 99%